Vprašanje narodne noše na Slovenskem - Knific, Bojan (Etnolog. Nova vrsta (Ljubljana), 2003)
The article deals with the development of national costumes in Slovenia as costumes for special occasions and defines their different forms and functions. The phenomenon of the national costume started in the mid 19th century in the developing Slovene bourgeois society, and it spread to the peasant population in the 1870s. The period between the two World Wars saw the most intensive development of the national costume because the "naša dečva" (our costume) campaign spread the national costume to all classes of the population.
Keywords: ethnology; etnologija; oblačilna kultura; zgodovinski pregledi; narodne noše; uniforme; kostumi